Formulasi Sediaan Moisturizer Gel Dari Sari Air Buah Mentimun (Cucumis Sativus L.) Kombinasi Buah Tomat (Solanum Lycopersicum L.) Sebagai Uji Efektivitas Pelembap Kulit - Enny Fitriani; Siti Aisyah Tanjung; Muhammad Bagas Fahriyansyah; Lintang Indah Kartini (STIKES Columbia Asia Medan, 2026)
Moisturizers are a type of cosmetic product that function to hydrate the skin by reducing water evaporation from the skin surface and attracting water from the air into the dehydrated stratum corneum. Ingredients that reduce water evaporation are known as occlusives, while those capable of attracting water into the skin layers are referred to as humectants. This study employed an experimental method with a purposive sampling technique. The samples used were aqueous extracts of cucumber fruit (Cucumis sativus L.) combined with tomato fruit (Solanum lycopersicum L.) juice, obtained from fresh fruits, followed by phytochemical screening to determine their secondary metabolite content. The preparation was formulated as a moisturizer gel with varying concentrations of the combined cucumber and tomato fruit extracts of 5%, 10%, and 15%. Physical quality tests were subsequently conducted, including organoleptic, homogeneity, pH, adhesion, spreadability, and irritation tests, as well as a moisturizer effectiveness test using a Skin Analyzer on volunteers. The results of the phytochemical screening showed that the combination of cucumber and tomato fruit extracts contained alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids, and glycosides. The moisturizer gel preparations containing the combination of cucumber and tomato fruit extracts demonstrated good stability, spread easily on the skin, did not cause irritation, and had a pH suitable for the skin. The effectiveness test showed that the highest increase in skin moisture was obtained at a concentration of 15%, with an average increase in moisture content of 72.11 ± 12.23%.